Basal carcinoma of the breast revisited: an old entity with new interpretations. Issue 5 (6th March 2008) - Korsching, E; Jeffrey, S S; Meinerz, W; Decker, T; Boecker, W; Buerger, H
Abstract : The introduction of global gene expression analysis in breast cancer research has focused attention onto a repeatedly described subgroup of invasive breast cancer, the basal-like carcinomas. This subgroup is characterised by the expression of high-molecular weight cytokeratins 5, 14 and 17; using immunohistochemical diagnosis, it represents approximately 7–20% of invasive breast cancers. Some of these tumours fulfil the criteria of grade 3 invasive ductal carcinoma, the so-called triple negative carcinomas. However, other rare subgroups of metaplastic, medullary and myoepithelial carcinomas also belong to this entity. Even though the initial clinical prognostic relevance of basal-like breast cancers may have been overestimated, its distinctive biology generates many questions regarding the pathogenesis, chemosensitivity and optimal clinical management of this subgroup. Physiological progenitor cells within the normal female breast share essential immunohistochemical features with basal-like breast cancers. Although the exact relationship between subgroups of normal breast cells and their respective malignant counterparts is still under investigation, the major hallmarks of physiological progenitor cells are either maintained or reactivated by distinct genetic changes in basal breast cancer cells. This review will discuss the impact of these findings on our global understanding of breast cancer pathogenesis, especially from the perspective of its potential histogenesis. Clinical consequences and potential future research directions driven by the definition of basal breast cancers will also be discussed.